1988
DOI: 10.2118/14392-pa
|View full text |Cite
|
Sign up to set email alerts
|

Sweep Improvement in CO2 Flooding by Use of Foaming Agents

Abstract: This study has two objectives:(1) to screen and select foaming agents for specific C02 floods and (2) to detennine the effectiveness of foam in improving sweep efficiency in CO 2 flooding. Foaming agents were evaluated on their ability to produce ample, lasting foam and to have low loss from adsorption on reservoir rock and decomposition at reservoir conditions. Foaming agents that perfonned well in shaking, blender, long-tenn stability, and high-pressure stability tests were selected for core-flow experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…Diversion of gas into lower-permeable layers using foams have previously been reported (e.g. Casteel and Djabbarah, 1988, Llave et al, 1990, Zerhboub et al, 1994, Nguyen et al, 2003. This may be important for fractured systems, where a very large permeability contrast exists and cross-flow between the zones occur (Bertin et al, 1999).…”
Section: Enhanced Oil Recovery In Fractured Reservoirsmentioning
confidence: 90%
“…Diversion of gas into lower-permeable layers using foams have previously been reported (e.g. Casteel and Djabbarah, 1988, Llave et al, 1990, Zerhboub et al, 1994, Nguyen et al, 2003. This may be important for fractured systems, where a very large permeability contrast exists and cross-flow between the zones occur (Bertin et al, 1999).…”
Section: Enhanced Oil Recovery In Fractured Reservoirsmentioning
confidence: 90%
“…As a result of its distinct flowing and rheological properties, the foam has been widely used as drilling fluid, fracturing fluid and acidizing fluid in the petroleum industry over the past decades (Bernadiner et al, 1992;Harris, 1995;Ozbayoglu et al, 2002). Nonetheless, perhaps its most attracting application is to offer the best hope for mobility control in gas flooding suffering from poor volumetric sweep efficiency due to the displacement front instability and early breakthrough caused by the undesirable gravity segregation and viscous fingering (Casteel and Djabbarah, 1988;Chen et al, 2005;Friedmann et al, 1991;Prigiobbe et al, 2016). This Enhanced Oil Recovery (EOR) technique is defined as the foam flooding.…”
Section: Résumé -éValuation Et Optimisation D'une Technique De Rah Hymentioning
confidence: 99%
“…It affects the interfacial forces between the gas and liquid which in turn affects value of Pc*. The proper surfactant should have the following properties: be capable of generating ample, lasting foam at the reservoir conditions, should have low adsorption and decomposition losses, should increase the sweep efficiency and the oil recovery, in addition it should be commercially available and inexpensive (Casteel and Djabbarah, [72]). Foam is readily formed during a drainage process (displacing the liquid phase by the gas phase) whenever the porous medium is pre-saturated with a surfactant solution (Chou, 1991).…”
Section: Surfactantmentioning
confidence: 99%
“…Adsorption of the surfactant on the reservoir rock reduces the surfactant concentration in the injected fluid. The adsorption is a function of the surfactant formulation, reservoir fluids, reservoir lithology, and reservoir conditions (Casteel and Djabbarah, [72]). For unconsolidated sand cores at temperatures ranging from 50˚C (122˚F) to 150˚C (302˚F) it was found that the surfactant adsorption decreases with increasing the temperature, and increases with the presence of clays in the core (Novosad et al, [75]).…”
Section: Surfactantmentioning
confidence: 99%
See 1 more Smart Citation